2009
DOI: 10.1089/dia.2008.0028
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postoperative Accuracy and Safety of a Real-Time Continuous Glucose Monitoring System in Cardiac Surgical Patients: A Randomized Pilot Study

Abstract: Although the RT-CGMS is safe and accurate according to accepted standards, there are still small aberrations, which in our opinion preclude unlimited use in its present form in a clinical setting. The effect of the alarm function at different glucose levels remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…Several studies have reported on the accuracy of CGM in critically ill patients. [39][40][41] Most of these studies included a small number of patients and limited their analysis to retrospective comparisons of a reference pointof-care value with CGM data. 38 The use of CGM may have an advantage over bedside point-of-care testing in that it has the potential to reduce the possibility of unknown hypoglycemic events that may occur between point-of-care measurements; however, some studies have raised concern on the accuracy of CGM at low BG levels and limited correlation between CGM and both capillary and arterial samples when the BG is less than 81 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the accuracy of CGM in critically ill patients. [39][40][41] Most of these studies included a small number of patients and limited their analysis to retrospective comparisons of a reference pointof-care value with CGM data. 38 The use of CGM may have an advantage over bedside point-of-care testing in that it has the potential to reduce the possibility of unknown hypoglycemic events that may occur between point-of-care measurements; however, some studies have raised concern on the accuracy of CGM at low BG levels and limited correlation between CGM and both capillary and arterial samples when the BG is less than 81 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Several clinical studies have indicated that utilization of CGM data, both retrospectively and in real time, can help adjust insulin therapies, prevent (or minimize the occurrence of) extreme glycemic excursions, 3,4 reduce glycated hemoglobin values, 5,6,7 and achieve a tight glycemic control in both intensive care 8,9 and surgical units. 10 Despite these clear advantages, utilization of CGM techniques is still limited in the current clinical practice, mainly because of concerns about their accuracy, reliability, robustness, and patient tolerability. As a direct consequence, tremendous research efforts from both the scientific community and medical diagnostics companies have been devoted to the development of accurate, reliable, minimally invasive, and automated CGM systems (CGMSs).…”
Section: Introductionmentioning
confidence: 99%
“…BMI, body mass index; EF, ejection fraction; WBC, white blood cell; HDL-C, high density lipoprotein-cholesterol; LDL-C, low density lipoprotein-cholesterol Data are reported as the mean ± SD or n (%). BMI, body mass index; EF, ejection fraction; WBC, white blood cell; HDL-C, high density lipoprotein-cholesterol; LDL-C, low density lipoprotein-cholesterol other studies argued that CGMS glucose values are not sufficiently accurate and reliable to be used for therapeutic decisions [30][31][32]. Currently, clinical experience with CGMS in CCUs is limited, particularly for STEMI patients undergoing p-PCI.…”
Section: Discussionmentioning
confidence: 99%